The medical threat of mamba envenoming in sub-Saharan Africa revealed by genus-wide analysis of venom composition, toxicity and antivenomics profiling of available antivenoms - Ainsworth, Stuart (2018)
Mambas (genus Dendroaspis) are among the most feared of the medically important elapid snakes found in subSaharan Africa, but many facets of their biology, including the diversity of venom composition, remain relatively understudied. Here, we present a reconstruction of mamba phylogeny, alongside genus-wide venom gland transcriptomic and high-resolution top-down venomic analyses. Whereas the green mambas, D. viridis, D. angusticeps, D. j. jamesoni and D. j. kaimosae, express 3FTx-predominant venoms, black mamba (D. polylepis) venom is dominated by dendrotoxins I and K. The divergent terrestrial ecology of D. polylepis compared to the arboreal niche occupied by all other mambas makes it plausible that this major difference in venom composition is due to dietary variation. The pattern of intrageneric venom variability across Dendroaspis represented a valuable opportunity to investigate, in a genus-wide context, the variant toxicity of the venom, and the degree of paraspecific cross-reactivity between antivenoms and mamba venoms. To this end, the immunological profiles of the five mamba venoms were assessed against a panel of commercial antivenoms generated for the sub-Saharan Africa market. This study provides a genus-wide overview of which available antivenoms may be more efficacious in neutralising human envenomings caused by mambas, irrespective of the species responsible. The information gathered in this study lays the foundations for rationalising the notably different potency and pharmacological profiles of Dendroaspis venoms at locus resolution. This understanding will allow selection and design of toxin immunogens with a view to generating a safer and more efficacious pan-specific antivenom against any mamba envenomation. Biological significance: The mambas (genus Dendroaspis) comprise five especially notorious medically important venomous snakes endemic to sub-Saharan Africa. Their highly potent venoms comprise a high diversity of pharmacologically active peptides, including extremely rapid-acting neurotoxins. Previous studies on mamba venoms have focused on the biochemical and pharmacological characterisation of their most relevant toxins to rationalize the common neurological and neuromuscular symptoms of envenomings caused by these species, but there has been little work on overall venom composition or comparisons between them. Only very recently an overview of the composition of the venom of two Dendroaspis species, D. angusticeps and D. polylepis, has been unveiled through venomics approaches. Here we present the first genus-wide transcriptomic-proteomic analysis of mamba venom composition. The transcriptomic analyses described in this paper have contributed 29 (D. polylepis), 23 (D. angusticeps), 40 (D. viridis), 25 (D. j. jamesoni) and 21 (D. j. kaimosae), novel full-length toxin sequences to the non-redundant Dendroaspis sequence database. The mamba genus-wide venomic analysis demonstrated that major D. polylepis venom components are Kunitz-fold family toxins. This feature is unique in relation to the relatively conserved three-finger toxin (3FTx)-dominated venom compositions of the green mambas. Venom variation was interpreted in the context of dietary variation due to the divergent terrestrial ecology of D. polylepis compared to the arboreal niche occupied by all other mambas. Additionally, the degree of cross-reactivity conservation of mamba venoms was assessed by antivenomics against a panel of commercial antivenoms generated for the sub-Saharan Africa market. This study provides a genus-wide overview to infer which available antivenoms may be capable of neutralising human envenomings caused by mambas, irrespective of the species responsible. The information gathered in this study lays the foundations for rationalising the pharmacological profiles of mamba venoms at locus resolution. This understanding will contribute to the generation of a safer and more efficacious pan-Dendroaspis therapeutic antivenom against any mamba envenomation.